PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF NEARPOD TERHADAP MINAT BELAJAR BAHASA INDONESIA SISWA KELAS X DI SMA NEGERI 1 SAMALANGA - Nadila, Sarah Ulfa; Astuti, Nia; Ezmar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by students' low interest in learning Indonesian. One effort to improve students' interest in learning is through the use of the Nearpod interactive learning media. This study aimed to determine the effect of using the Nearpod interactive learning media on the interest in learning Indonesian among tenth-grade students at SMA Negeri 1 Samalanga. The study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The population consisted of 180 tenth-grade students at SMA Negeri 1 Samalanga. The sample comprised 30 students in the experimental class and 30 students in the control class. Data were collected through tests, questionnaires, and documentation. The data were analyzed using descriptive statistics, normality tests, homogeneity tests, the Independent Sample t-Test, and the N-Gain test. The results showed that the mean posttest score of the experimental class was 83.33, which was higher than that of the control class (73.50). The results of the Independent Sample t-Test yielded a significance value (Sig. 2-tailed) of 0.001 < 0.05, indicating that the use of the Nearpod interactive learning media had a significant effect on students' interest in learning. Furthermore, the N-Gain score of 0.75 was categorized as high. Based on these findings, it can be concluded that the Nearpod interactive learning media has a significant effect on students' interest in learning Indonesian among tenth-grade students at SMA Negeri 1 Samalanga. In addition, the N-Gain results indicate that the media is also effective in improving students' interest in learning.